Dorsal raphe serotonergic neurons preferentially reactivate dorsal dentate gyrus cell ensembles associated with positive experience - Yuma Nagai; Yuri Kisaka; Kento Nomura; Naoya Nishitani; Chihiro Andoh; Masashi Koda; Hiroyuki Kawai; Kaoru Seiriki; Kazuki Nagayasu; Atsushi Kasai; Hisashi Shirakawa; Takanobu Nakazawa; et al. (Cell Reports, 2023)
Summary: Major depressive disorder (MDD) is among the most common mental illnesses. Serotonergic (5-HT) neurons are central to the pathophysiology and treatment of MDD. Repeatedly recalling positive episodes is effective for MDD. Stimulating 5-HT neurons of the dorsal raphe nucleus (DRN) or neuronal ensembles in the dorsal dentate gyrus (dDG) associated with positive memories reverses the stress-induced behavioral abnormalities. Despite this phenotypic similarity, their causal relationship is unclear. This study revealed that the DRN 5-HT neurons activate dDG neurons; surprisingly, this activation was specifically observed in positive memory ensembles rather than neutral or negative ensembles. Furthermore, we revealed that dopaminergic signaling induced by activation of DRN 5-HT neurons projecting to the ventral tegmental area mediates an increase in active coping behavior and positive dDG ensemble reactivation. Our study identifies a role of DRN 5-HT neurons as specific reactivators of positive memories and provides insights into how serotonin elicits antidepressive effects.